Cassava (Manihot esculenta) starch films reinforced with natural fibrous filler - Versino, Florencia (2014)
The remaining fibrous residue of cassava starch extraction was characterized and used as film filler in order to obtain an enhanced fully biodegradable starch-based composite. Film-forming gelatinized cassava starch suspensions increased significantly their apparent viscosity and storage modulus with filler addition, although no segregation of filler particles was observed. Homogenous films were obtained from 3% w/w cassava starch film-forming suspensions including glycerol as plasticizer and the remaining fibrous residue. Plasticizer concentration was optimized in reinforced starch films. SEM micrographs evidenced that the filler was structurally incorporated in the matrix, although concentrations of 3% led to more heterogeneous surfaces because of the presence of large size filler particles. Reinforced films exhibited UV-barrier capacity and adequate water vapor barrier properties (14.6 ± 0.7 10−11 g/m s Pa) and tensile strength (18.01 ± 0.19 MPa) when 25% w/w glycerol was added as plasticizer. Filler addition reinforced the starch matrix increasing its mechanical resistance: 1.5% residue content increased over 900% the films elastic modulus. Furthermore, the obtained eco-compatible materials could be heat sealed, which indicates their suitability for packaging development. In conclusion, an integral approach to cassava roots use has been proposed, expanding its scope and providing added value to the remaining residue of starch extraction.